IDENTIFYING THE FACTORS AFFECTING ENVIRONMENTAL ENTREPRENEURSHIP WITH AN EMPHASIS ON THE TRADITIONAL TEXTURES OF HISTORICAL CITIES - Sara Jamshidi (PalArch's Journal of Archaeology of Egypt / Egyptology, 2021)
The aim of present study was to identify the factors affecting environmental entrepreneurship with an emphasis on the traditional textures of historical cities. The research method was descriptive-survey. Statistical population of study included 260 experts of Cultural Heritage, Handicrafts and Tourism Organization, Iranian Department of Environment, municipalities of Hamedan. In the present study, 152 subjects were randomly selected using stratified random sampling method. A researcher-made questionnaire was used to collect research data. The validity and reliability of questionnaire were examined and confirmed by the researcher during the research process. Research data were collected based on research questions and analyzed using exploratory factor analysis and confirmatory factor analysis in SPSS19 and LISREL software. The results revealed that 6 economic, environmental, cultural, social, political and personal factors had a positive and significant impact on environmental entrepreneurship with an emphasis on the traditional textures of historical cities.